The Influence of Competence and Compensation on Organizational Citizenship Behavior (OCB) and Employee Performance of the Indonesian Red Cross in Banten Province - Tata Rustandi*; Udin Suadma; Ayu Pratami (Universitas Syiah Kuala, 2023)
This study aimed to determine and analyze the influence of Competence and compensation on Organizational Citizenship Behavior (OCB) on the Performance of Indonesian Red Cross Employees in Banten Province. This study uses data collection methods with a quantitative approach. The measurement scale used in the questionnaire in this study is the interval scale, which is a data measuring tool that produces data with a range of values that have meaning, even though the absolute value is less significant. The interval scale used agree-disagree. The test results show that Competency on Employee Performance is T_statistic = 5.363 ≥ 1.96 with a P-Value of 0.000 0.05. It is concluded that there is a significant influence between Competence and Employee Performance. Compensation for Employee Performance of T_statistik = 3.248 ≥ 1.96 with a P-Value of 0.001 ≤ 0.05 concluded that there is a significant positive effect between Compensation and Employee Performance. Competency on Organizational Citizenship Behavior (OCB) of T_statistik = 5.591 ≥ 1.96 with a P-Value of 0.000 ≤ 0.05 concluded that there is a significant positive effect between Competence on Organizational Citizenship Behavior (OCB). Compensation for Organizational Citizenship Behavior (OCB) of T_statistik = 5.807 ≥ 1.96 with a P-Value of 0.000 ≤ 0.05 concluded that there is a significant positive effect between Compensation on Organizational Citizenship Behavior (OCB). Organizational Citizenship Behavior (OCB) on Employee Performance of T_statistik = 5.706 ≥ 1.96 with a P-Value of 0.000 ≤ 0.05 concluded that there is a significant influence between Organizational Citizenship Behavior (OCB) and Employee Performance.